Application of polyethylenimine-coated magnetic nanocomposites for the selective separation of Cs-enriched clay particles from radioactive soil. Issue 37 (8th June 2020) - Kim, June-Hyun; Kim, Sung-Man; Yoon, In-Ho; Kim, Ilgook
Abstract : Selective separation of Cs-enriched fine particles from contaminated soil using Fe3 O4 -PEI nanocomposites and a mesh filter. Abstract : The separation of Cs-enriched fine particles is a highly effective way to reduce the volume and radioactivity of contaminated soil. This work demonstrated the application of polyethylenimine (PEI)-coated Fe3 O4 nanocomposites and a mesh filter for the selective separation of clay particles from Cs-contaminated soil. The PEI coating on the Fe3 O4 nanoparticles enhanced the binding force between the magnetic nanoparticles and clay minerals via electrostatic attraction; thus, approximately 100% of the clay particles were magnetically separated from solution by Fe3 O4 -PEI nanocomposites at a low dose (0.04 g-nanocomposite per g-clay). In separation experiments with soil mixtures, clay- and silt-sized fine particles that had been magnetized by Fe3 O4 -PEI nanocomposites were selectively separated, and the separation efficiency improved when a mesh filter was added to exclude physically large particles. The combination of magnetic and sieving separation thoroughly separated fine particles from soil by reducing the volume of the magnetic fraction. We also evaluated the magnetic-sieving separation method for the selective removal of clay particles from 137 Cs-contaminated soil. The decrease in radioactivity in the treated nonmagnetic fraction, which accounted for 87.5% of the total soil, corresponded to a high decontamination efficiency of approximately 90%. The developed separation technology offers great potential for the efficient remediation of radioactive soil.